2022
DOI: 10.1371/journal.pntd.0010214
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiological survey of Coxiella burnetii in livestock and humans in Tana River and Garissa counties in Kenya

Abstract: Background Coxiella burnetii is a widely distributed pathogen, but data on its epidemiology in livestock, and human populations remains scanty, especially in developing countries such as Kenya. We used the One Health approach to estimate the seroprevalance of C. burnetii in cattle, sheep, goats and human populations in Tana River county, and in humans in Garissa county, Kenya. We also identified potential determinants of exposure among these hosts. Methods Data were collected through a cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Seroprevalences of 6.5% using complement fixation test and 32% using commercial ELISA kit were reported in Malawi and Cameroon’s Adamawa region cattle by Staley et al ( 33 ) and Scolamacchia et al ( 31 ), respectively. Mwololo et al ( 13 ) reported a seroprevalence of 3.00% in cattle in Kenya’s Tana River and Garissa counties using iELISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seroprevalences of 6.5% using complement fixation test and 32% using commercial ELISA kit were reported in Malawi and Cameroon’s Adamawa region cattle by Staley et al ( 33 ) and Scolamacchia et al ( 31 ), respectively. Mwololo et al ( 13 ) reported a seroprevalence of 3.00% in cattle in Kenya’s Tana River and Garissa counties using iELISA.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has been reported worldwide except in New Zealand, and there are a few reports of C. burnetii infection in South African livestock ( 10 , 11 ). Q fever seroprevalence in cattle has been reported in Zimbabwe ( 12 ), Kenya ( 13 ), Algeria ( 14 ) and in Nigeria ( 15 ). In the Netherlands the economic costs of the Q fever outbreak (2007–2010) in about 4,000 human cases acquired from infected dairy goat farms were estimated to be ~0.307 billion EUR ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study presents large overall seroprevalence compared to other two studies conducted in northern Africa by Horton et al (2014) and Derdour et al (2017). It aligns with the findings by Depuy et al (2014) in Kenya and reports lower seroprevalence compared to those reported in other three African countries (Adamu et al, 2018;Deressa et al, 2020;Kazwala 2016;Larson et al, 2019;Mwololo et al, 2015;Kelly et al, 2021;Ameur et al, 2018;Menadi et al, 2020). Additionally a recent systematic review of Q fever in domestic ruminants in Africa reported a seroprevalence range estimates of 3-89.7% in East Africa both in dairy and local breeds of cattle (Bwatota et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Cadmus et al [32] reported 61.3% seroprevalence for C. burnetii from 137 individuals screened from Sokoto, while 12.0% seroprevalence was reported in Taraba [25]. A similar finding from the studies conducted outside Nigeria in Tana and Garissa in Kenya indicated a prevalence of 24.44% for C. burnetii from 974 individuals screened [60], while a lower prevalence of 2.3% was reported in western Kenya [61].…”
Section: Coxiella Burnetii Infection In Northern Nigeriamentioning
confidence: 76%